1989
DOI: 10.3109/00048678909068290
|View full text |Cite
|
Sign up to set email alerts
|

Christchurch Psychiatric Epidemiology Study, Part II: Six Month and other Period Prevalences of Specific Psychiatric Disorders

Abstract: The Christchurch Psychiatric Epidemiology Study determined the occurrence (over 2 weeks, 1 month, 6 months, 12 months and life-time) of a number of specific DIS/DSM-III psychiatric diagnoses in the Christchurch urban area. Data were collected on 1498 randomly selected adults, aged between 18 and 64 years. The Diagnostic Interview Schedule (DIS) was used to collect information to make a DSM-III diagnosis. The six month prevalence rates of disorder are presented and compared with available results from the NIMH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
1
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(63 citation statements)
references
References 37 publications
6
55
1
1
Order By: Relevance
“…Numerous studies have reported higher levels of trait anxiety in mothers compared to fathers (Franck et al, 2004;Pinelli, 2000) as well as higher rates of depression in women compared to men, with a gender ratio of 3 : 1 commonly reported (Henderson et al, 1998;Oakley-Browne, Joyce, Wells, Bushnell, & Hornblow, 1989). Similarly, higher levels of the personality dimensions-harm avoidance, reward dependence and cooperativeness in mothers-are consistent with those of other studies examining gender differences in personality (Cloninger, 1994;Young et al, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…Numerous studies have reported higher levels of trait anxiety in mothers compared to fathers (Franck et al, 2004;Pinelli, 2000) as well as higher rates of depression in women compared to men, with a gender ratio of 3 : 1 commonly reported (Henderson et al, 1998;Oakley-Browne, Joyce, Wells, Bushnell, & Hornblow, 1989). Similarly, higher levels of the personality dimensions-harm avoidance, reward dependence and cooperativeness in mothers-are consistent with those of other studies examining gender differences in personality (Cloninger, 1994;Young et al, 1995).…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were reported by Oakley-Browne et al [ 17] from New Zealand. In an epidemiological study of women living in Edin burgh.…”
Section: Incidence Of a Dsupporting
confidence: 81%
“…The best-estimate rates for 1-year and lifetime prevalence were 2.6% (95%CI, 1.4% to 4.2%) and 6.2% (95%CI, 4.0% to 9.2%), respectively ( (55). Heterogeneity was demonstrated for 1-year and lifetime prevalence rates of GAD.…”
Section: Generalized Anxiety Disordermentioning
confidence: 95%